Effects of Essential Oils on Feed Efficiency, Digestion, Ruminal Fermentation, Milk Production, and Milk Composition in Dairy Cows - Hayrettin Çayıroğlu (Turkish Journal of Agriculture: Food Science and Technology)
Essential oils are secondary compounds obtained from several parts of plants. They play an important role in the protection of the plants as antibacterials, antivirals, antifungals, insecticides in nature. Along with the prohibition of the use of antibiotics as feed additives in a lot of countries around the world, scientists have accelerated the search for safer and more natural feed additive. In this respect, essential oils and their active components have come to the fore as an alternative feed ingredient. In this review, effects of essential oils on feed intake, feed efficiency, nutrient digestibility, rumen fermentation, milk yield and its composition in dairy cattle were evaluated.